Test case minimizing based on combination chaos genetic algorithm - Qing SHEN; Yunliang JIANG; Zhangguo SHEN; Jungang LOU (Dianxin kexue)
Test case minimizing is one of the most important research fields in software testing.Uniformly distributed Chebyshev and Logistic chaos sequence were introduced in the selection，crossover and mutation of genetic algorithm.Chaos disturbance was also added in genetic testing suite to address the common problems of weak ability in local search and premature convergence，thus to optimize the test result.Experiments were conducted in randomly generated test suites and Siemens test suites.Comparisons were also made with classical methods regard to the scale of production of test suite and the execution time of the algorithms.The results of the experiment indicate that based on the same execution time of the algorithms，a smaller scale test suite can be produced by introducing chaotic sequence in genetic testing suite selection.